Numerical Modelization for Equilibrium Position of a Static Loaded Hydrodynamic Bearing - Le, Anh Dung; Tran, Thi Thanh Hai; Luu, Trong Thuan (Old Journal, 2020)
This paper presents a numerical simulation of hydrodynamic journal bearing lubrication by using finite element method to solve Reynolds equation in static load condition. Reynolds boundary condition is applied in this research in order to yield oil film pressure distribution at a given oil supply hole position. When the pressure distribution is obtained, the equilibrium position of the housing bearing can be determined by using Newton-Raphson method applied on the equilibrium equation of the charge. The equilibrium positions are simulated in different parameters of the journal speed and the applied load. The results show that at the different sections of bearing, the starting disruption positions are different and the middle section along the axial direction shows the maximum pressure and gradually decreases toward two ends of bearing. On the other hand, the more loads applied, the distance from the calculated equilibrium position to the journal center gets farther. The faster journal rotation speed makes the balance point closer to the journal center.